IMPLEMENTASI MBKM “MENGAJAR DI SATUAN PENDIDIKAN” DI TAMAN KANAK-KANAK NEO GENESIS - Dwiyanti, Ni Made Christine; Karta, Ni Luh Putu Agustini; Suarthana, I Ketut Putra; Asih, Anak Agung Ketut Sri (Synergy and Society Service, 2024)
This community service learning program is an implementation of the Independent Learning Independent Campus Learning (MBKM) "Teaching in Educational Units" with the object of service at PAUD and Neo Genesis Kindergarten. The goal of this activities are encourage the students to be more familiar with their natural environment. The methodology of this community service learning are to apply PjBL and PBL learning to PAUD and Kindergarten School, so that students are more familiar with the environment. The results of this community service learning program are provide a positive response for students of the natural environment, interact and do activities in nature through handling common cases. In this service, the PjBL project is to invite children to harvest rice and problem-based learning (PBL) is a case of analyzing why plants wilt. The results of learning are the formation of structured concepts and mindsets in analyzing problems and practicing them in everyday life. The conclusion of this community service learning activities is that the PjBL and PBL learning methods are able to further develop students' cognitive and psychomotor aspects towards the natural environment.